Association between diabetes and the outcome of root canal treatment in adults: an umbrella review. (19th December 2019) - Nagendrababu, V.; Segura‐Egea, J. J.; Fouad, A. F; Pulikkotil, S. J.; Dummer, P. M. H.
Abstract: Background: Diabetes mellitus is the most common metabolic disorder amongst dental patients. The association between the diabetes and the outcome of root canal treatment is unclear. Aim: To conduct an umbrella review to determine whether there is an association between diabetes and the outcome of root canal treatment. Data source: The protocol of the review was developed and registered in the PROSPERO database (CRD42019141684). Four electronic databases (PubMed, EBSCHOhost, Cochrane and Scopus databases) were used to perform a literature search until July 2019. Study eligibility criteria, participants and interventions: Systematic reviews with or without meta‐analyses published in English assessing any outcomes of root canal treatment comparing diabetic and nondiabetic patients were included. Two reviewers were involved independently in study selection, data extraction and appraising the reviews that were included. Disagreements were resolved with the help of a third reviewer. Study appraisal and synthesis methods: The quality of the reviews was assessed using the AMSTAR tool (A measurement tool to assess systematic reviews), with 11 items. Each AMSTAR item was given a score of 1 if the criterion was met, or 0 if the criterion was not met or the information was unclear. Results: Four systematic reviews were included. The AMSTAR score for the reviews ranged from 5 to 7, out of a maximum score of 11, and all the systematic reviews were classified as 'medium' quality. Limitations: Only two systematic reviews included a meta‐analysis. Only systematic reviews published in English were included. Conclusions and implications of key findings: Diabetes mellitus is associated with the outcome of root canal treatment and can be considered as a preoperative prognostic factor.